Performance of sub-standard reinforced concrete barriers in protecting bridge piers against vehicular collision force - Salahat, Fahed H. S. (Kansas State University, 2023)
An important purpose of using Reinforced Concrete (RC) barriers in the highway inventory is to act as railing that protects bridge piers against vehicular collision force (VCF). These barriers are designed to absorb the collision energy and/or redirect the vehicle away from the parts being protected. According to the bridge design specifications of the American Association of State Highway Transportation Officials (AASHTO), barriers used to protect bridge piers should have a minimum height of 1067 mm and survive MASH Test Level 5 (TL-5). Many existing barriers that are currently used in roadways do not meet this requirement, hereby, they are referred to as "sub-standard" barriers. While these barriers are found to be inadequate to solely protect bridge piers against VCF, their presence to intervene vehicle-pier collisions will contribute to reducing the severity of the crash effects. Consequently, they reduce the VCF demand that AASHTO specifies for piers to resist when upgrading existing bridges. This research aims at assessing the performance of sub-standard RC barriers as protective structures to bridge piers against VCF and quantifying their contribution towards reducing the Equivalent Static Force (ESF) that piers required to resist as per the modern AASHTO specifications. The research will present existing procedures in determining the transverse static capacity of RC barriers and propose alternative and accurate methodologies to predict this capacity. Also, a matrix of crash scenarios is simulated in dynamic explicit analysis through the multi-purpose finite element software LS-DYNA to obtain a comprehensive idea about the behavior of sub-standard RC barriers. The investigated parameters include energy dissipation, velocity reduction, contact force absorption and lateral displacement. Finally, a bridge pier that was found to be deficient to address the VCF under the required AASHTO’s ESF is used in a simulation matrix behind the sub-standard barrier. A series of Dynamic Impact Force (DIF) time histories are obtained and used to extract the Equivalent Static Force (ESF). Comparing the resulting ESF with the force required by AASHTO, a reduction in the ESF due to the presence of sub-standard RC barriers is proposed. The main findings of this research revealed that the existing procedure used by AASHTO to determine the transverse static capacity of RC barriers might, in some cases, result in about 50% capacity underestimation. Also, the inadequacy of sub-standard barriers in absorbing and/or redirecting the impacting vehicle refers to geometrical deficiency (insufficient height). In other words, the sub-standard barrier can resist high impact load demands and protect the piers behind if sufficient height, such as 1070 mm for TL-4, exists to prevent contact between the impacting vehicle and the piers. Finally, the presence of sub-standard barriers might cause a reduction in the ESF that AASHTO requires bridge piers to resist by at least 25%.
Keywords: RC barriers; Yield line analysis; Finite element analysis; LS-DYNA; Vehicle collision; Dynamic finite element analysis; Vehicular collision force; Bridge piers; AASHTO